The return of black box economics - a critique of Keen on effective demand and changes in debt - Reissl, Severin (Düsseldorf, 2019)
"In a paper for the Review of Keynesian Economics, Steve Keen recently provided a restatement of his claim that "effective demand equals income plus the change in debt". The aim of the present article is to provide a detailed critique of Keen's argument using an analytical framework pioneered by Wolfgang Stützel which has recently been developed further.Using this framework, it is shown that there is no strictly necessary relationship whatsoever between effective demand and changes in the level of gross debt. Keen's proposed relation is shown not to hold under all circumstances, and it is demonstrated that where it does hold this is due to variations in the `velocity of debt'-variable he introduces. This variable, however, lacks theoretical underpinning. The article also comments on Keen's proposal that trade in financial assets should be included in effective demand, arguing that this undermines the concept of effective demand itself. It is also shown that many weaknesses in Keen's argument stem from a lack of terminological clarity which originates in his interpretation of the works of Hyman Minsky."